The credit card debt puzzle: The role of preferences, credit risk, and financial literacy - Olga Gorbachev; María José Luengo-Prado (Federal Reserve Bank of Boston, 2016)
We use the 1979 National Longitudinal Survey of Youth to revisit what is termed the credit card debt puzzle: why consumers simultaneously co-hold high-interest credit card debt and lowinterest assets that could be used to pay down this debt. This dataset contains unique information on intelligence, financial literacy, and preferences, while also providing a complete picture of households' balance sheets. Relative to individuals with no credit card debt but positive liquid assets, individuals in the puzzle group have higher discount rates, slightly lower financial literacy scores, and very different perceptions on future credit risk: many individuals are using credit cards for precautionary motives.
Keywords: D14; D91; E21; G02; 330; household finance; risk aversion; time preferences; precautionary motives; bankruptcy; foreclosure